Synthesis, spectroscopic [IR, (1H, 13C, 27Al) NMR] and mass spectrometric studies of aluminium(III) complexes containing O- and N-chelating Schiff bases - Dubey Raj Kumar; Meenakshi; Singh Avadhesh Pratap (Main Group Metal Chemistry, 2015)
Reactions of aluminium isopropoxide with 2-(o-hydroxyphenyl)-benzoxazole (pboxH) and salicylidene-4-chloroaniline (spcaH) in different molar ratios in benzene solution afforded the complexes of the types [(μ-OPri)2Al2(pbox)2(OPri)2] 1, [Al(OPri)(pbox)2] 2, [Al(pbox)3] 3, [(μ-OPri)2Al2(spca)2(OPri)2] 4, [Al(OPri)(spca)2] 5 and [Al(spca)3] 6. All these colored solid complexes are soluble in common organic solvents and were characterized by elemental (C, H, N and Al) analysis, spectroscopic [IR (1H, 13C and 27Al) NMR] and mass spectrometric studies. On the basis of these studies, plausible structures have been tentatively proposed for these complexes.